Heterogeneity of cough hypersensitivity mediated by TRPV1 and TRPA1 in patients with chronic refractory cough - Long, Li (Respir Res, 2019)
BACKGROUND: The differential sensitivity of cough to antitussive therapies implies the existence of heterogeneity in cough hypersensitivity, but how such heterogeneity is expressed across individual patients is poorly understood. We investigated the phenotypes of cough hypersensitivity by examining transient receptor potential ankyrin 1 (TRPA1)- and transient receptor potential vanilloid 1 (TRPV1)-mediated cough sensitivity in patients with chronic refractory cough. METHODS: Using a selective TRPA1 agonist, allyl isothiocyanate (AITC), we established an AITC cough challenge as a measure of TRPA1-mediated cough sensitivity. The AITC cough challenge and the widely used capsaicin (a selective TRPV1 agonist) cough challenge were performed with 250 patients with chronic refractory cough and 56 healthy subjects. The concentration of AITC or capsaicin solution causing at least two (C2) and five coughs (C5) was recorded. Cough sensitivity was expressed as the mean (95% confidence interval) of log C5, and cough hypersensitivity was defined as a log C5 value lower than that of healthy subjects. RESULTS: A distinct concentration–response effect of inhaled AITC was identified both in patients with chronic refractory cough and in healthy subjects. Cough sensitivity to AITC and capsaicin was significantly higher in patients than in healthy subjects (AITC: 2.42 [2.37–2.48] vs 2.72 [2.66–2.78] mM, p = 0.001; capsaicin: 1.87 [1.75–1.98] vs 2.53 [2.36–2.70] μM, p = 0.001) and was higher in females than in males for both healthy subjects and patients (all p < 0.05). Among the 234 patients who completed both challenges, 25 (10.7%) exhibited hypersensitivity to both AITC and capsaicin, 44 (18.8%) showed hypersensitivity to AITC only, 28 (11.9%) showed hypersensitivity to capsaicin only, and 137 (58.6%) exhibited hypersensitivity to neither. Those with TRPA1- and/or TRPV1-mediated hypersensitivity were predominantly female, while those without TRPA1- and TRPV1-mediated hypersensitivity were mainly male. CONCLUSIONS: Four phenotypes of cough hypersensitivity were identified by the activation of TRPV1 and TRPA1 channels, which supports the existence of heterogeneity in cough pathways and provides a new direction for personalized management of chronic refractory cough. TRIAL REGISTRATION: ClinicalTrials.gov NCT02591550.